Reliability And Validity Of A Clinically Calculated Muscle Power Test: A Quasi-Isometric Approach Correlated With Functional Sit-To-Stand Test (The Review of Diabetic Studies, 2025)
Background: Accurate assessment of muscle power is essential for understanding the functional activity in clinical populations. Functional tests, like Single leg Sit-To-Stand test 5 repetition, offer a clinical estimation of lower-limb muscle power, but it is not applicable to all clinical conditions. Quasi-isometric test presents a quiet, simple, and low-cost alternative that may be possible for people with limited mobility.Objective: The objective of the present study was to evaluate the test-retest reliability of a clinically calculated quasi-isometric muscle power test and to examine the concurrent validity by analysing the correlation between quasi-isometric muscle power and functional muscle power from the SLST5rept test using the Alcazar et al. (2018) equation.Method: A quasi-experimental design was used. Lower-limb muscle power was measured in two methods. Quasi-isometric muscle power was determined, with the right and left sides tested, via two trials, using a clinical set, and power values were derived from force and lever arm measurements. Functional muscle power was derived from the SLST5rept test of the Alcazar formula, which takes into account body mass, gravitational acceleration, body height, and task completion time. Descriptive statistics were performed on all variables. The reliability of the test for quasi-isometric muscle power was determined by the comparison of repeated tests, whereas the concurrent validity was evaluated by the Pearson's correlation coefficient between the two power measures, namely quasi-isometric vs. SLST5rept, based muscle power.Results: The quasi-isometric muscle power test displayed an excellent test-retest reliability (ICC=0.99), as the differences between repeated trials and sides were minimal. In contrast, correlation analysis revealed a weak and insignificant relationship between quasi-isometric muscle power and functional muscle power from the SLST5rept (r = 0.08), indicating a very poor concurrent validity between two measurement methods.Conclusion: The study concludes that the clinically calculated quasi-isometric muscle power test is a highly reliable assessment method, but showed poor concurrent validity when compared to functional sit-to-stand method. This can be interpreted as quasi-isometric, and functional sit-to-stand muscle power tests are not interchangeable. The use of both methods together improves the clinical evaluation of lower-limb muscle function and functional performance.